Pengaruh Cafe Atmosphere, Menu Variation dan Price Terhadap Kepuasan Pengunjung Resto Super Geprek Sape Kabupaten Bima - Hairunisa Hairunisa; Muhajirin; Feni Aryani (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of cafe atmosphere, menu variation, and price on customer satisfaction at Super Geprek Sape Restaurant in Bima Regency. The study used a quantitative approach with an associative research type. The study population was all customers at Super Geprek Sape Restaurant in Bima Regency, with a sample of 96 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of the SPSS program. Data analysis included validity tests, reliability tests, classical assumption tests, correlation coefficients, determination coefficients, t-tests, and F-tests. The results showed that cafe atmosphere, menu variation, and price had a positive and significant effect on customer satisfaction, both partially and simultaneously. These findings indicate that a comfortable restaurant atmosphere, diverse menu variations, and prices that are in accordance with the quality of products and services are important factors in increasing customer satisfaction. These three variables were able to explain 37.8% of the variation in customer satisfaction, while the rest was influenced by other factors outside the study. Thus, improving the quality of the restaurant atmosphere, menu innovation, and appropriate pricing can be effective strategies to increase customer satisfaction.